2016
DOI: 10.1002/eji.201545987
|View full text |Cite
|
Sign up to set email alerts
|

Activation of murine invariant NKT cells promotes susceptibility to candidiasis by IL‐10 induced modulation of phagocyte antifungal activity

Abstract: Invariant NKT (iNKT) cells play an important role in a variety of antimicrobial immune responses due to their ability to produce high levels of immune-modulating cytokines.Here, we investigated the role of iNKT cells in host defense against candidiasis using Jα18-deficient mice (Jα18 −/− ), which lack iNKT cells. Jα18 −/− mice were more resistant to the development of lethal candidiasis than wild-type (WT) mice. In contrast, treatment of WT mice with the iNKT cell activating ligand α-galactosylceramide markedl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Enhanced secretion of IL-10 has been reported to increase susceptibility of mice to infections by mycobacterial and fungal pathogens (6367). Moreover, blocking IL-10 production enhanced the protective efficacy of BCG vaccination against M. tuberculosis infection (68).…”
Section: Mincle Modulates Inflammatory Responsesmentioning
confidence: 99%
“…Enhanced secretion of IL-10 has been reported to increase susceptibility of mice to infections by mycobacterial and fungal pathogens (6367). Moreover, blocking IL-10 production enhanced the protective efficacy of BCG vaccination against M. tuberculosis infection (68).…”
Section: Mincle Modulates Inflammatory Responsesmentioning
confidence: 99%
“…3a, the concentrations of serum IL-6, IL-10, and TNF-α in ABX group were significantly higher than those in the CNV group, whereas the levels of IL-17A, IFN-γ, IL-12, and IL-22 were significantly decreased. A previous study has shown that administration of IL-10 increased host susceptibility to candidiasis [54], while IL-17, IFN-γ, IL-12, and IL-22 played an important role in protecting against candida [55].…”
Section: Inflammatory Response Was Aggravated In Abx Mice During Invamentioning
confidence: 94%
“…i NKT cells contribute to the pathogenesis of C. albicans infection, the most frequent Candida species. Following systemic C. albicans infection, Jα18-deficient mice lacking i NKT cells exhibited a higher survival rate and a lower fungal burden in various organs than wild-type (WT) mice because of the increased accumulation of macrophages and neutrophils in the peritoneal cavity ( 52 ). Consistent with the amelioration of infection by i NKT cell depletion, IL-10 levels were lower and IL-12p40 levels were higher in the serum of C. albicans -infected Jα18-deficient mice than infected WT mice.…”
Section: Nkt Cells Contribute To the Pathogenesis Of Some mentioning
confidence: 99%
“…Consistent with the amelioration of infection by i NKT cell depletion, IL-10 levels were lower and IL-12p40 levels were higher in the serum of C. albicans -infected Jα18-deficient mice than infected WT mice. Conversely, NKT cell transfer exacerbated C. albicans infection in Jα18-deficient mice concomitant with reduced accumulation of macrophages and neutrophils ( 52 ). Furthermore, IL-10 treatment exacerbated C. albicans infection in Jα18-deficient mice, and transfer of IL-10-deficient NKT cells into Jα18-deficient mice significantly increased survival following C. albicans infection compared to the transfer of WT NKT cells ( 52 ).…”
Section: Nkt Cells Contribute To the Pathogenesis Of Some mentioning
confidence: 99%
See 1 more Smart Citation